Dotawo: A Journal of Nubian Studies 5: Nubian Women (Punctum Books, 2018)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and the critical and theoretical approaches of postcolonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet the internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of older kingdoms. Volume 5 of Dotawo focuses on Nubian women, both ancient and contemporary. Nubian women, whether they were queens or commoners, Christians or Muslims, have always been held in high esteem by their communities. The contributors to this volume present articles which address Nubian literature, tomb and temple wall paintings, the challenges of migration and resettlement, cultural tourism, gender roles, women's health, labor cooperatives, and more. They all focus on the ways in which Nubian women have survived and thrived throughout the centuries.